Edukasi Kesehatan tentang Tuberkulosis: Membangun Komitmen Masyarakat untuk Pengendalian TBC - Kasmawati, Henny; Hikmah, Nurull; Trinovitasari, Nita; Jannah, Sitti Raodah Nurul; Malina, Rachma; Suryani, Suryani; Nuralifah, Nuralifah; Aswani, Aswani (JIPITI: Jurnal Pengabdian kepada Masyarakat, 2025)
Tuberculosis (TB) is an infectious disease that is still a global health problem, caused by the bacterium Mycobacterium tuberculosis, which is acid-resistant and mainly attacks the lungs, but can also attack other organs. This disease can affect people of all ages, including babies, children, adults, and the elderly. TB transmission occurs through the air from people who cough or sneeze, with the main factors affecting public health being environmental factors and behaviours, such as uncovered coughing and poor sanitation. TB cases in Southeast Sulawesi Province have shown a significant upward trend in recent years, with the incidence rate continuing to rise every year. The success of TB treatment is influenced by a variety of factors, including medication adherence, which is a major challenge to avoid the emergence of drug resistance, such as TB-MDR. The Government of Indonesia has issued policies and focuses on reducing TB incidence through education and socialisation to encourage active community involvement in TB control to achieve the national target by 2030.